PERANCANGAN PROTOTIPE GOKART GASIX SEBAGAI MEDIA PEMBELAJARAN SISTEM MOTOR LISTRIK PADA MATA KULIAH TEKNOLOGI KENDARAAN LISTRIK DI LABORATORIUM PVTO UNIVERSITAS PGRI YOGYAKARTA - Ibnu Fajar; Bayu Gilang Purnomo (Journal of Automotive Technology Vocational Education, 2025)
The study titled Design of a Gasix Go-Kart Prototype as a Learning Medium for Electric Motor Systems in the Electric Vehicle Technology Course at PGRI Yogyakarta University aims to develop and evaluate instructional media for electric motor system learning at the UPY PVTO Lab. The objectives of this research are: (1) to produce appropriate and feasible learning media for electric motor systems used in the Electric Vehicle Technology course, (2) to determine the effectiveness of the developed media in supporting student learning, and (3) to identify obstacles encountered during the design process of the Gasix Go-Kart–based learning media.This study adopts the Four-D (4D) development model. Define, Design, Develop, and Disseminate introduced by Thiagarajan, Semmel, and Semmel (1974). The research was conducted at the UPY PVTO Lab with 10 students as participants. Data were collected using interview guidelines and questionnaires, including assessments from media experts, material experts, and student response questionnaires. The results show that the designed learning media meet feasibility standards. Material expert validation yielded a score of 88%, while media expert validation reached 76%, placing the product in the “appropriate for use” category. Furthermore, student response tests indicate that the media are highly effective, achieving an 82% score categorized as "very effective.” Challenges encountered during development relate primarily to time constraints and the selection of target respondents. Time limitations affected stages such as design, production, validation, dissemination, and evaluation. Meanwhile, determining suitable respondents required careful selection to ensure alignment with the research objectives and characteristics needed for accurate feedback.   Keywords: media, electric motor system, Gasix gokart, electric vehicle technology.